Study on activity, stability limit and reaction mechanism of CO self-sustained combustion over the LaMnO3, La0.9Ce0.1MnO3 and La0.9Sr0.1MnO3 perovskite catalysts using sugar agent. (15th May 2021) - Huang, Junqin; Teng, Zihao; Kang, Running; Bin, Feng; Wei, Xiaolin; Hao, Qinglan; Nam Hui, Kwun; San Hui, Kwan; Dou, Baojuan
Highlights: The LMO-W, LMO-SW, LCMO-W, LCMO-SW, LSMO-W and LSMO-SW catalysts were well designed by precursors. The Binary search was used to determine the lean-combustion limits for the self-sustained combustion of CO. The stability of the LCMO-SW catalyst was evaluated under CO oxidation at the furnace temperature of 535 °C. The influence mechanism of self-sustaining combustion stability of CO catalyst was investigated and put forward. The L-H mechanisms were performed for SCR reaction over the catalysts via in situ IR experiments. Abstract: The LaMnO3, La0.9 Ce0.1 MnO3 and La0.9 Sr0.1 MnO3 catalysts are synthesized using sugar agent, and the CO self-sustained combustion is investigated, where the catalytic performance is decided by temperature with CO conversions of 10% (T10 ), 50% (T50 ), and 90% (T90 ). The results show that self-sustaining combustion is successfully realized on the catalyst, and the order of activity decrease is as follows: La0.9 Ce0.1 MnO3 (with sugar) > La0.9 Sr0.1 MnO3 (with sugar) > LaMnO3 (with sugar) > LaMnO3 (without sugar) > La0.9 Sr0.1 MnO3 (without sugar) > La0.9 Ce0.1 MnO3 (without sugar). Combined with the results of XPS, H2 -TPR, O2 -TPD and CO-TPD techniques, the excellent activity of La0.9 Ce0.1 MnO3 (with sugar) can be attributed to the high content of Mn 4+ ions and reactive oxygen vacancies enriched on the catalyst surface, sound low-temperature reduction, and uniform dispersion. Besides, in situ IR spectroscopy results indicate that the catalytic combustion of CO over manganese-based perovskite catalysts follows the L-H mechanism: the chemisorption of CO and O2 takes place to produce monodentate carbonates and bicarbonate species, which then decompose to yield CO2 release. The high-temperature stability test provides evidence that the La0.9 Ce0.1 MnO3 (with sugar) gives 100% CO conversion and that the activities remain almost unchanged after reaction for 12 h, where the temperature of catalyst bed reaches about 717 °C. The results obtained are helpful to accept this technology on efficient and clean energy utilization in iron and steel industry.